A "Whirlpool of Gain": French Aristocrats and Atlantic Merchants in Northern European Port Cities after 1789. Issue 3 (1st December 2022) - Polasky, Janet
Abstract: The thousands of aristocratic emigrants from revolutionary France who found asylum in the independent German city city-state of Hamburg and the neighboring Danish city of Altona were not the only immigrants arriving in the neutral ports. Alongside these flamboyant newcomers, merchants, scholars, artisans, and others continued, as they had for decades, to come in pursuit of the economic opportunities denied them at home. With harbors on the Elbe River just downstream from the North Sea, the two cosmopolitan port cities flourished as wars and revolution roiled the rest of Europe. Diplomatically neutral and open to trade, these two cities opened their doors to newcomers from around the world. Over the decade, the aristocrats, who thought themselves cosmopolitan, tested their welcome in the prosperous ports with no native nobility. While most of the newcomers assimilated readily, contributing to the ports' prosperity, the aristocrats left to reclaim what remained of their estates.